Impact of Business Intelligence on Business Performance of Food Delivery Platforms in Sri Lanka (Global Journal of Management and Business Research, 2020)
The purpose of this research is to determine if business intelligence has an impact on the business performance of the food delivery platforms in Sri Lanka An analysis of the 178 responses from the employees of Uber EATS and Pick Me Food concluded that business intelligence has a statistically significant impact on the business performance of the food delivery platform
Keywords: business intelligence; business performance; COVID-19; food delivery platform